The Hybrid Photovoltaic-Thermoelectric Generator Configurations for Energy Performance Improvement - A. U, Saleh; Jumaat, Siti Amely (International Journal of Integrated Engineering, 2022)
Photovoltaic-thermoelectric generator is an integrated hybrid system, which enables optimal thermal management of PV and hence increases overall efficiency. The rise in temperature is one of the most challenging issues influencing the efficiency of photovoltaic systems resulting in significant thermal fluctuations affecting the hybrid system life span. PV cell cooling is a principal research aim that many researchers have focused their attention on. Thermoelectric generators used to improve photovoltaic efficiency are amongst the widely adopted thermal management systems. Photovoltaic cells convert the solar irradiance directly into electrical energy while the thermoelectric generator uses the heat not used by the PV, which results in parasitic loss of electricity. The current hybrid system, as in the spectrum splitting method, has shown promises of improvement. But, lack the practicality to be deployed to the mass market, which is due to the complex structure that is not feasible to be turned into a consumer product. At the same time, the direct method contributes to adding a little heat to the PV. Thus, reducing the total hybrid system efficiency, as such both lack the capacity needed for active cooling. However, with our proposed sandwich coupling method where the PV will be placed at the top of roofing shingle, the TEG under the shingle. The TEG will use heat not utilized by the PV, which cause excess heat in the PV cells to produce additional energy. At the same time, the shingle stabilizes the thermal fluctuation, thus Increasing total hybrid power output and efficiency. The system will provide a practical, real-life application. Our preliminary results show the significant improvement in power output generated with the double side heat sink.